2023
DOI: 10.1371/journal.pgph.0001451
|View full text |Cite
|
Sign up to set email alerts
|

Non-adherence to the World Health Organization’s physical activity recommendations and associated factors among healthy adults in urban centers of Southwest Ethiopia

Abstract: Physical inactivity is a major risk-factor of non-communicable diseases. The World Health Organization has set physical activity recommendations for adults to reduce physical inactivity and its consequences. However, 1.4 billion adults are non-adherent to the recommendation worldwide. The prevalence of non-adherence to this recommendation and its predictors has not been assessed in urban Ethiopia. This study aimed to determine the prevalence of non-adherence to physical activity recommendations and identify it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…There is a dearth of literature on the link between happiness and patients' treatment adherence. A community-based study showed that nonadherence to health recommendations such as physical activity had a link to lower level of happiness, [23] an association which the present study equally showed. Patients who reported higher levels of happiness also showed greater level of adherence to treatment regimen.…”
Section: Annals Of Health Research Volume 9 Issue No 4 2023__________...supporting
confidence: 70%
“…There is a dearth of literature on the link between happiness and patients' treatment adherence. A community-based study showed that nonadherence to health recommendations such as physical activity had a link to lower level of happiness, [23] an association which the present study equally showed. Patients who reported higher levels of happiness also showed greater level of adherence to treatment regimen.…”
Section: Annals Of Health Research Volume 9 Issue No 4 2023__________...supporting
confidence: 70%
“…To enable this determination of adequacies of self-care physical activity and healthy diet, yardsticks have been set by the WHO guidelines for physical activity and sedentary life ( 2020b ) as well as studies that have shown the effectiveness of culturally modified Mediterranean diet to reduce Type 2 Diabetes risk by Duncan et al ( 2020 ) and Bavaro et al ( 2021 ). Despite the set standards, for physical activity and diet, a study in Ethiopia found that 61% of older PLWH do not adhere to WHO ( 2020b ) standards of physical activity because of a lack of participation in community engagement activities (Zenu et al 2023 ). In light of the inadequate physical activity and dietary patterns by older PLWH reported in Ethiopia by Zenu et al ( 2023 ) and Uganda by Wright et al ( 2021 ) respectively, this study seeks to provide a description of current practices in Harare which enables focused health education where there are inadequacies.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the set standards, for physical activity and diet, a study in Ethiopia found that 61% of older PLWH do not adhere to WHO ( 2020b ) standards of physical activity because of a lack of participation in community engagement activities (Zenu et al 2023 ). In light of the inadequate physical activity and dietary patterns by older PLWH reported in Ethiopia by Zenu et al ( 2023 ) and Uganda by Wright et al ( 2021 ) respectively, this study seeks to provide a description of current practices in Harare which enables focused health education where there are inadequacies. Furthermore, studies that have described self-care practices in older PLWH have been conducted in other contexts, creating a paucity of literature from Harare urban district.…”
Section: Introductionmentioning
confidence: 99%